Uncovering ethics in bioscience - Anise Younis, Harry Witchel (BioScientist: The Salford Biomedicine Society Magazine, 2024)
Ethics is a recurrent conversation in science, with the advancement of new technologies, cellular research and clinical trials, we find ourselves asking how well the population of service users are really protected. Nowadays, concerns arise about how well our privacy is being protected and how our consent and safeguarding is being prioritised. While the additions of new laws and regulations aim to protect human rights, they raise the all-important question in the world of bioethics about the responsibility of scientists and institutions: How well can these organisations ensure the protection of service users while keeping pace with novel scientific inventions? This article had a contribution from and has been reviewed by Professor Harry Witchel, a renowned Doctor of Physiology and Neuroscience, currently teaching at Brighton and Sussex Medical School. By sharing his expertise, he has provided a better understanding of ethics and decision making of scientists over time. The Editorial Team would like to thank Prof Witchel for his time and expertise that he has shared.